Teacher Burnout and Self Esteem in Tangerang's Junior High School Teachers - Sovitriana, Rilla; Santosa, Agus Djoko; Hendrayani, Febi (International Review of Management and Marketing, 2019)
This study aims to test the theoretical model of social support, job satisfaction and interpersonal communication's influence to burnout, with self-esteem as the mediator in junior high school teachers in South Tangerang. The total respondents were 287 teachers in South Tangerang area. The study is using purposive sample, with non-probability sampling. Data analysis is using SEM (Structural Equation Model) Lisrel (Linear Structural Relationship) program 8.72. The hypothesis concludes "theoretical model of social support, job satisfaction and interpersonal communication's influence to burnout with self-esteem as mediator, fit with empirical data. Practical suggestion is, teachers should obtain social support, job satisfaction and interpersonal communication to avoid the burnout. Keywords: Teacher Burnout, Social Support, Job Satisfaction, Interpersonal Communication and Self-esteem JEL Classifications: A21, I21, I25 DOI: https://doi.org/10.32479/irmm.7641